An Analysis of Students Learning Style in Enhancing English Vocabulary in The Digital Era - Islam, Raudhatul; Musdalifah; Rizqiyah, Nur Vina (ITScience (Information Technology and Science), 2025)
The research followed a descriptive framework to examine how Generation Z learns vocabulary, particularly focusing on their everyday vocabulary learning styles in the context of the current digital age. Hence, a qualitative approach was chosen for this study. The research subjects here are Generation Z, specifically seventh-semester students of the English Education Department at Zainul Hasan Genggong Islamic University. The instruments used in this study such as observation, interviews, and documentation. The reseult of this research showed the learning styles of Generation Z students in acquiring English vocabulary are significantly influenced by the use of digital technology. The dominant learning style is a combination of visual, auditory, and kinesthetic approaches, all of which are supported by various digital platforms and applications. Students demonstrate a strong interest in visual and audio-based learning media, such as images, videos, and sounds, which are available through applications like Vocabulary.com and Duolingo, as well as platforms such as YouTube, Tik Tok, and Instagram. This indicates a preference for an audio-visual learning style.